Assessment of the Immune Response Induced in Neonatal Calves by Vaccination with Mycobacterium Bovis BCG Phipps Under Field Conditions - Fernando Díaz Otero; Laura Jaramillo Meza; José Ángel Gutiérrez Pabello; Felipe Ángel Castañeda Cuevas; Camila Arriaga Díaz; Xochitl Eva González González; Ricardo Lascurain; Eve-Lyne Quevillon (Journal of Veterinary Healthcare, 2017)
Immunization of cattle with the bacillus Calmette-Guérin (BCG) vaccine, especially neonates, induces protection against Mycobacterium bovis (M. bovis) and has been proposed as a strategy for bovine tuberculosis (bTB) control. Therefore, the aim of this study was to evaluate the immune response induced under field conditions in neonatal calves vaccinated with BCG Phipps, a strain that has rarely been evaluated in the bovine population, using interferon (IFN)-γ and tuberculin tests, flow cytometry and enzyme-linked immunosorbent assay. Two groups (vaccinated and control) of 5 calves were monitored for 12 weeks, and increases in the in vitro IFN-γ production, the percentage of cluster of differentiation (CD)8+ T cells and the activation levels of CD4+ and CD8+ T cells were observed 3 to 4 weeks post-vaccination. Bovine purified protein derivative-specific IFN-γ production was increased about 4.8- and 5.5-fold in vaccinated animals compared to non-vaccinated animals 3 and 4 weeks post-vaccination respectively. CD8+ T cells of the vaccinated group were increased 1.6-, 1.5- and 1.6-fold at weeks 2, 3 and 4 respectively. Levels of activation were 1.7- and 1.9-fold higher for CD4+ T cells and 2.3- and 1.8-fold higher for CD8+ T cells in the vaccinated group at weeks 3 and 4 respectively in response to M. bovis antigens. However, no animals (vaccinated or control) showed positive results for the single intradermal comparative tuberculin test (SICTT). Therefore, our results indicate that vaccination with M. bovis BCG Phipps strain stimulated peripheral blood T cell activity and induced a cell-mediated immune response. In addition, vaccination did not interfere with the SICTT, as previously reported, which indicates that this vaccine could be successfully applied in bTB control campaigns.
Keywords: BCG Phipps